2010
DOI: 10.4269/ajtmh.2010.10-0168
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Outbreaks of Puffer Fish Intoxication in Bangladesh, 2008

Abstract: During April and June 2008, we investigated three outbreaks of marine puffer fish intoxication in three districts of Bangladesh (Narshingdi, Natore, and Dhaka). We also explored trade of marine puffer fish in Cox's Bazaar, a coastal area of the country. We identified 95 people who had consumed puffer fish; 63 (66%) developed toxicity characterized by tingling sensation in the body, perioral numbness, dizziness, and weakness, 14 of them died. All three outbreaks were caused by consumption of large (0.2–1.5 kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 10 publications
1
27
0
1
Order By: Relevance
“…Yet another study by Khora in 1991, reported that skin of the pufferfishes were most toxic. Lee et al, in 2003 reported that TTX is accumulated in the pufferfishes through their food chain and indeed the toxicity varies depending on this factor too. Khora in 1994 reported that pufferfishes raised in captivity are non toxic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet another study by Khora in 1991, reported that skin of the pufferfishes were most toxic. Lee et al, in 2003 reported that TTX is accumulated in the pufferfishes through their food chain and indeed the toxicity varies depending on this factor too. Khora in 1994 reported that pufferfishes raised in captivity are non toxic.…”
Section: Discussionmentioning
confidence: 99%
“…Pufferfishes produce a potent neurotoxin named Tetrodotoxin (TTX) which is a sodium channel blocker in cell membranes. Reports indicated that TTX is much similar to saxitoxin (STX), which causes paralytic shellfish poisoning (How et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4,5,8,[15][16][17] Only one study explored the use of pufferfish in the coastal region and the inhabitants' understanding about puffer toxicity and epidemiologic information. 12 Because the number of outbreaks being reported increased in 2008, it was important to explore if there had been recent changes in availability of pufferfish and its use.…”
Section: Introductionmentioning
confidence: 99%
“…9 Seven outbreaks of marine pufferfish poisoning have been reported in national newspapers, scientific articles, and unpublished work throughout Bangladesh during 1998-June 2008, which affected 156 persons and caused 40 deaths (case-fatality rate = 26%). 3,4,[12][13][14] However, most investigations have been limited to quantitative epidemiologic outbreak analysis, which primarily focused on the immediate risk factors associated with illness, and to signs and symptoms of case-patients and their management; a few studies highlighted the toxicologic characteristics of pufferfish. 1,4,5,8,[15][16][17] Only one study explored the use of pufferfish in the coastal region and the inhabitants' understanding about puffer toxicity and epidemiologic information.…”
Section: Introductionmentioning
confidence: 99%